Bead embroidery - Cox, Shelley (Teacher) (Essential stitch guide., 2021)
Part of the wonderful Royal School of Needlework Essential Stitch Guides, this book focuses on bead embroidery. It includes a brief history, basic techniques, counted thread embroidery, bead embroidery, surface embroidery and fringes. The book is illustrated with fine examples of work, many from the author's private collection. It details everything you need to know with step by step instructions and photographs of techniques that make it all so much easier. Stitches are included with instructions, a good-sized clear photograph and a chart. It is suitable for those needing to learn basic beading. - Yarnsandfabrics.co.uk/crafts.